Angiopoietin‐like 4: A molecular link between insulin resistance and rheumatoid arthritis. Issue 5 (8th March 2017) - Masuko, Kayo
ABSTRACT: Recent evidence suggests that common factor(s) or molecule(s) might regulate lipid and glucose metabolism, inflammation, and bone and cartilage degeneration. These findings may be particularly relevant for cases of rheumatoid arthritis, in which chronic inflammation occurs in an autoimmune context and causes the degradation of articular joints as well as insulin resistance and cardiovascular complications. Candidates for this common regulatory system include signals mediated by peroxisome proliferator‐activated regulator and its response factor, angiopoietin‐like 4. The expression and bioactivity of angiopoietin‐like 4, an adipocytokine that was originally reported to have an angiogenic function, have been detected not only in the vascular system and adipose tissue but also in rheumatoid joints. An essential role for angiopoietin‐like 4 has been established in dyslipidemia, and recent reports indicate that it may modulate bone and cartilage catabolism in rheumatoid arthritis. The enhanced expression of angiopoietin‐like 4 in rheumatoid arthritis may explain the occurrence of insulin resistance, cardiovascular risk, and joint destruction, thereby suggesting that this molecule could be a potential target for anti‐rheumatoid arthritis strategies. This review describes recent research on the role of angiopoietin‐like 4 in chronic inflammatory conditions and rheumatoid arthritis, as well as potential therapeutic candidates. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:939–943, 2017.